Equine neorickettsiosis: A global perspective of the natural habitat of the bacteria and clinical disease - Luis G. Arroyo; Alexandre S. Borges; John D. Baird; Brian D. Perry; Yasuko Rikihisa; Stephen E. Greiman (Veterinary Microbiology, 2026)

Novel resistance to tobacco etch virus in peppers (Capsicum spp.) - Kevin M. Crosby; Sixto A. Marquez; Olufemi Alabi; Kevin Ong; Stephen Perry (Euphytica, 2025)
Tobacco etch virus (TEV) is a pathogen that affects peppers all over the world. It causes serious losses, and it is difficult to control since it has many aphid vectors. Because these aphids move around, and transmit TEV in a non-persistent manner, many applications of pesticides would be necessary to reduce TEV incidence, leading to more environmental pollution and destruction of beneficial predator insects. Therefore, host plant resistance is the best solution for TEV. Peppers ( Capsicum spp.) exhibit ample genetic variability. Numerous resistance genes against TEV have been documented over the past 70 years. However, these are all recessive in nature. This has made deployment in hybrids more difficult and therefore, not many TEV resistant pepper cultivars have been released. The pepper breeding project at Texas A&M AgriLife Research screened over 200 USDA plant introductions from 6 species for resistance to TEV with both natural field infection and controlled inoculations at Weslaco. ELISA tests and visual assessments of symptoms of the virus in the plants were performed. Four accessions not previously characterized as resistant were identified with mild or no symptoms. These included two C. chinense and two C. baccatum accessions. An interspecific population of C. annuum ‘serrano’ x C. baccatum var. baccatum was developed to study the resistance from that wild type. Chi-square analysis indicated that resistance is controlled by a single, dominant gene, which will facilitate the development of resistant varieties using traditional breeding procedures such as backcrossing.

Effects of fungicide application on the foliar endophytic fungi of Scots pine (Pinus sylvestris) - Joanne E. Taylor; Karsten Schönrogge; Anna Oliver; Stephen Cavers; Joan Cottrell; Annika Perry; Melanie Gibbs; Richard Ennos (Fungal Ecology, 2025)

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Disentangling a genome-wide mosaic of conflicting phylogenetic signals in Western Rattlesnakes - Justin M. Bernstein; Yannick Z. Francioli; Drew R. Schield; Richard H. Adams; Blair W. Perry; Keaka Farleigh; Cara F. Smith; Jesse M. Meik; Stephen P. Mackessy; Todd A. Castoe (Molecular Phylogenetics and Evolution, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

The suppression of lower leg electromyography when walking in textured foot orthoses - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

Threats to the persistence of sugar pine (Pinus lambertiana) in the western USA - Daniel E. Foster; Scott S. Stephens; Perry de Valpine; John J. Battles (Forest Ecology and Management, 2024)

Capitalizing on skin in orthotics design: the effects of texture on plantar intrinsic foot muscles during locomotion - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

The topographical attenuation of cutaneous input is modulated at the ankle joint during gait - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2024)

The effect of texture under distinct regions of the foot sole on human locomotion - Kelly A. Robb; Stephen D. Perry (Experimental Brain Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Annotated expression and activity data for murine recombinase alleles and transgenes: the CrePortal resource - Michelle N. Perry; Constance M. Smith; Hiroaki Onda; Martin Ringwald; Stephen A. Murray; Cynthia L. Smith (Mammalian Genome, 2022)
Recombinase alleles and transgenes can be used to facilitate spatio-temporal specificity of gene disruption or transgene expression. However, the versatility of this in vivo recombination system relies on having detailed and accurate characterization of recombinase expression and activity to enable selection of the appropriate allele or transgene. The CrePortal ( http://www.informatics.jax.org/home/recombinase ) leverages the informatics infrastructure of Mouse Genome Informatics to integrate data from the scientific literature, direct data submissions from the scientific community at-large, and from major projects developing new recombinase lines and characterizing recombinase expression and specificity patterns. Searching the CrePortal by recombinase activity or specific recombinase gene driver provides users with a recombinase alleles and transgenes activity tissue summary and matrix comparison of gene expression and recombinase activity with links to generation details, a recombinase activity grid, and associated phenotype annotations. Future improvements will add cell type-based activity annotations. The CrePortal provides a comprehensive presentation of recombinase allele and transgene data to assist researchers in selection of the recombinase allele or transgene based on where and when recombination is desired.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Molecular signatures of divergence and selection in closely related pine taxa - Witold Wachowiak; Julia Zaborowska; Bartosz Łabiszak; Annika Perry; Giovanni M. Zucca; Santiago C. González-Martínez; Stephen Cavers (Tree Genetics & Genomes, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Genetic structure in the European endemic seabird, Phalacrocorax aristotelis , shaped by a complex interaction of historical and contemporary, physical and nonphysical drivers - Evanthia Thanou; Stefano Sponza; Emily J. Nelson; Annika Perry; Sarah Wanless; Francis Daunt; Stephen Cavers (Molecular Ecology, 2017)
Geographically separated populations tend to be less connected by gene flow, as a result of physical or nonphysical barriers preventing dispersal, and this can lead to genetic structure. In this context, highly mobile organisms such as seabirds are interesting because the small effect of physical barriers means nonphysical ones may be relatively more important. Here, we use microsatellite and mitochondrial data to explore the genetic structure and phylogeography of Atlantic and Mediterranean populations of a European endemic seabird, the European shag, Phalacrocorax aristotelis , and identify the primary drivers of their diversification. Analyses of mitochondrial markers revealed three phylogenetic lineages grouping the North Atlantic, Spanish/Corsican and eastern Mediterranean populations, apparently arising from fragmentation during the Pleistocene followed by range expansion. These traces of historical fragmentation were also evident in the genetic structure estimated by microsatellite markers, despite significant contemporary gene flow among adjacent populations. Stronger genetic structure, probably promoted by landscape, philopatry and local adaptation, was found among distant populations and those separated by physical and ecological barriers. This study highlights the enduring effect of Pleistocene climatic changes on shag populations, especially within the Mediterranean Basin, and suggests a role for cryptic northern refugia, as well as known southern refugia, on the genetic structure of European seabirds. Finally, it outlines how contemporary ecological barriers and behavioural traits may maintain population divergence, despite long‐distance dispersal triggered by extreme environmental conditions (e.g. population crashes).

Hybrid plants preserve unique genetic variation in the St Helena endemic trees Commidendrum rotundifolium DC Roxb. and C. spurium (G.Forst.) DC - Alan Gray; Annika Perry; Stephen Cavers; Antonia Eastwood; Michelle Biermann; Andrew Darlow; Vanessa Thomas; Phil Lambdon (Conservation Genetics, 2017)

Long-term dynamics of watershed leaching and lake sediment sequestration of rare earth elements following deglaciation of two mountain watersheds - Stephen A. Norton; Marie-Claire Pierret; Jiří Kopáček; Michael J. Handley; Randall H. Perry (Journal of Paleolimnology, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

Determining the influence of environmental and patient specific factors on the polymicrobial communities of the cystic fibrosis airway - Andrew Nelson; Audrey Perry; John D. Perry; Stephen J. Bourke; Stephen P. Cummings; Anthony De Soyza (Antonie van Leeuwenhoek, 2013)

Effects of a novel mGlu2/3 receptor agonist prodrug, LY2140023 monohydrate, on central monoamine turnover as determined in human and rat cerebrospinal fluid - Stephen Lowe; Robert Dean; Bradley Ackermann; Kimberley Jackson; Fanni Natanegara; Shelby Anderson; James Eckstein; Eunice Yuen; Mosun Ayan-Oshodi; Mary Ho; David McKinzie; Kenneth Perry; et al. (Psychopharmacology, 2012)

The controls on phosphorus availability in a Boreal lake ecosystem since deglaciation - Stephen A. Norton; Randall H. Perry; Jasmine E. Saros; George L. Jacobson; Ivan J. Fernandez; Jiří Kopáček; Tiffany A. Wilson; Michael D. SanClements (Journal of Paleolimnology, 2011)

Observing Biogeochemical Cycles at Global Scales with Profiling Floats and Gliders: Prospects for a Global Array - Kenneth Johnson; William Berelson; Emmanuel Boss; Zanna Chase; Hervé Claustre; Steven Emerson; Nicolas Gruber; Arne Körtzinger; Mary Jane Perry; Stephen Riser (Oceanography, 2009)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)

Deconstruction of Historic Mercury Accumulation in Lake Sediments, Northeastern United States - Ethan Perry; Stephen A. Norton; Neil C. Kamman; P. M. Lorey; Charles T. Driscoll (Ecotoxicology, 2005)

Mapping of a discontinuous and highly conformational binding site on follicle stimulating hormone subunit-β (FSH-β) using domain Scan™ and Matrix Scan™ technology - Peter Timmerman; Evert Van Dijk; Wouter Puijk; Wim Schaaper; Jerry Slootstra; Stephen J. Carlisle; John Coley; Steve Eida; M. Gani; Tim Hunt; Paul Perry; Gerry Piron; et al. (Molecular Diversity, 2004)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Tumor Necrosis Factor-Alpha in Normal and Diseased Brain: Conflicting Effects Via Intraneuronal Receptor Crosstalk? - Seth W Perry; Stephen Dewhurst; Matthew J Bellizzi; Harris A Gelbard (Journal of NeuroVirology, 2002)

Transferring soils from high‐ to low‐elevation forests increases nitrogen cycling rates: climate change implications - Stephen C. Hart; David A. Perry (Global Change Biology, 1999)
We assessed the potential impact of global warming resulting from a doubling of preindustrial atmospheric CO 2 on soil net N transformations by transferring intact soil cores (0–15 cm) from a high‐elevation old‐growth forest to a forest about 800 m lower in elevation in the central Oregon Cascade Mountains, USA. The lower elevation site had mean annual air and soil (10‐cm mineral soil depth) temperatures about 2.4 and 3.9 °C higher than the high‐elevation site, respectively. Annual rates of soil net N mineralization and nitrification more than doubled in soil transferred to the low‐elevation site (17.2–36.0 kg N ha –1 and 5.0–10.7 kg NO 3 – –N ha –1 , respectively). Leaching of inorganic N from the surface soil (in the absence of plant uptake) also increased. The reciprocal treatment (transferring soil cores from the low‐ to the high‐elevation site) resulted in decreases of about 70, 80, and 65% in annual rates of net N mineralization, nitrification, and inorganic N leaching, respectively. Laboratory incubations of soils under conditions of similar temperature and soil water potential suggest that the quality of soil organic matter is higher at the high‐elevation site. Similar in situ rates of soil net N transformations between the two sites occurred because the lower temperature counteracts the effects of greater substrate quantity and quality at the high elevation site. Our results support the hypothesis that high‐elevation, old‐growth forest soils in the central Cascades have higher C and N storage than their low‐elevation analogues primarily because low temperatures limit net C and N mineralization rates at higher elevations.